Return on Investment of Public Support to SMEs and Innovation in Poland - World Bank (World Bank, Washington, DC, 2020)
A Smarter Europe is a top priority of the European Union (EU), the core of which is innovation, economic transformation, and more competitive small and medium enterprises (SMEs). These themes account for a huge part of EU spending in the past, present, and future programming periods. Despite high expenditures, impacts on the economy often appear modest or are not well understood. EU, national, and regional policymakers want to know where and how to invest to get the highest return on investment (ROI). Poland was selected as the pilot country, since it is the largest recipient of EU funding, and has a rich set of support measures and implementing bodies. The remainder of the document is organized as follows. Section 2 summarizes the assessment of the needs of the Polish ecosystem, along with the portfolio mapping and policy mix analysis. Section 3 summarizes the functional analysis methodology and findings. Section 4 describes the ROI/effectiveness methodology and findings. And Section 5 offers conclusions and recommendations based on the combined analyses.